Geostatistics with Applications in Earth Sciences - Sarma, D. D.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2009)
This book has been designed to serve as a text book for post graduate-students and research workers in earth sciences who require a background of and a feel for statistics and the theory of regionalised variables. The book is titled 'Geostatistics with Applications in Earth Sciences". This new edition has been completely revised to reflect the notable concept - and technique-wise in geostatistics. Chapter 1 has been expanded and incorporates more detials on sampling and sampling designs. Chapters 2 and 5 have been extensively revised and a new chapter "Introduction to Advanced Geostatistics" has been added. Also new are the "Review Questions" at the end of each chapter. Audience: This book will be of interest to post-graduate students and researchers in Earth sciences. - Written from the perpective of the mining industry - Includes codes for six computer programs - Worked examples and review questions are added at the end of each chapter From the reviews of the previous edition: ... It would be particularly useful as a quick reference text and, along with others of its ilk, as a resource for individuals who might want to ramp up quickly in the field of geostatistics. (T.C. Coburn, Mathematical Geology, vol. 36, no. 8, 2004).
Statistical Methods in Earth Sciences -- Univariate Statistical Methods, Frequency Analysis and Simulation -- Some Statistical Distributions -- Stochastic Modelling (Time Series Analysis) and Forecasting -- Concepts of Regionalised Variables and Variogram Modelling -- Regularised Models, Volume-Variance Relationships and Economics -- The Concepts of Dispersion, Extension and Estimation Variances -- Kriging Variance and Kriging Procedure -- to Advanced Geostatistics -- Computer Software.
Keywords: Earth sciences; Geology -- Statistical methods; Mineral resources; Earth Sciences; Earth Sciences, general; Mineral Resources; Quantitative Geology; Electronic books